THE SOCIO-TECHNICAL ENTANGLEMENTS OF LIVE STREAMING ON TWITCH.TV - Johnson, Mark Richard; Woodcock, Jamie (AoIR Selected Papers of Internet Research, 2018)
The website and platform Twitch.tv is the overwhelming market leader in the live broadcast (“streaming”) of user-created videos over the internet, known primarily for the streaming of video game play. In both 2016 and 2017 over two million people regularly broadcast on the platform, resulting in over a million years of video content in total viewed by over one hundred million people (Twitch, 2017). The deep newness of this phenomenon, alongside the many elements that constitute it, make it an important site for studying digital labour, co-production, and gaming culture. In this paper we focus on three elements of the conference theme: the shifting political and creative economies of streaming media, in our case Twitch; social media, platforms, podcasts, and actors in online networks; and the materialities of data, in our case a million years of video content. Specifically, we consider the entangling of the technical and social dimensions of the Twitch phenomenon: how these elements shape the labour of Twitch streamers, audience engagement with the platform, and Twitch’s wider position in contemporary media production. To do so we draw upon semi-structured interviews with over one hundred professional streamers on the Twitch platform, lasting between ten minutes and one hour, alongside at least one hour of ethnographic observation from over two hundred Twitch channels and ethnographic work from almost a dozen gaming events in the United Kingdom, United States, Germany and Poland in the past two years.